A Study of Imparities between Chinese Painting and Western Painting from Perspectives of Arts and Cultures - Xuan, Qilin (Journal of Literature and Arts Research, 2025)
In the context of global art history, Chinese and Western painting have developed as two of the most influential artistic traditions, shaped by their unique cultural, philosophical, and historical trajectories. This study examines the disparities between Chinese and Western painting, rooted in their distinct historical evolutions and cultural philosophies. It investigates the materials, tools, artistic purposes, and expressions of space that define these traditions. Chinese painting reflects harmony between nature and humanity, often employing symbolic representation and leaving space for subjective imagination. In contrast, Western painting values realism, with detailed depictions of the natural and human worlds rooted in rational observation. The analysis highlights the influence of Taoist, Confucian, and Buddhist philosophies on Chinese art, while Western painting derives inspiration from religious themes and humanism. By comparing these distinct systems, this study underscores the richness of global artistic diversity and advocates for cultural appreciation and mutual learning.